Caffeine combined with sodium bicarbonate improves pacing and overall performance during a high-intensity time trial - Correia-Oliveira, C.; Lopes-Silva, J. P. (Research Quarterly for Exercise and Sport, 2023)
Background: No study has demonstrated the effects of sodium bicarbonate plus caffeine (NaHCO3 + CAF) on power output (PO) distribution (e.g., pacing), physiological parameters and energy system contribution during a 4-km cycling time trial (TT). Thus, we aimed to investigate the effects of NaHCO3 + CAF on pacing, physiological parameters, and energy system contribution during a 4-km cycling TT.